Epigenetic effects on eye diseases. (April 2012) - Hewitt, Alex W; Wang, Jie Jin; Liang, Helena; Craig, Jamie E
Epigenetics is the process by which patterns of gene expression are modified in a mitotically heritable manner. However, these epigenetic variations are not attributable to changes in the primary nucleotide sequence within DNA. In this review, the emerging field of epigenetics is introduced and the potential role it may have in the manifestation of common ocular disease is explored. Given our current understanding of the genetic, environmental and phenotypic profiles, it is probable that stochastic epigenetic effects have an important role in the pathogenesis of age-related macular degeneration, glaucoma, cataract and myopia. The ability to profile individuals at an epigenetic level offers a novel means to intimately dissect gene–environment interactions.